2015
DOI: 10.1038/tpj.2015.83
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics and induction/consolidation therapy toxicities in acute lymphoblastic leukemia patients treated with AIEOP-BFM ALL 2000 protocol

Abstract: Drug-related toxicities represent an important clinical concern in chemotherapy, genetic variants could help tailoring treatment to patient. A pharmacogenetic multicentric study was performed on 508 pediatric acute lymphoblastic leukemia patients treated with AIEOP-BFM 2000 protocol: 28 variants were genotyped by VeraCode and Taqman technologies, deletions of GST-M1 and GST-T1 by multiplex PCR. Toxicities were derived from a central database: 251 patients (49.4%) experienced at least one gastrointestinal (GI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 38 publications
2
50
0
3
Order By: Relevance
“…The ITPA variant allele (rs1127354) is associated with nonfunctionality of the enzyme and is found with an allelic frequency ranging from 5 to 19%, with the lower end of the range seen in Caucasian populations and the higher range seen in Asian populations [96]. The polymorphism is associated with higher concentrations of methylated nucleotide metabolites of 6-MP in cells, as well as higher incidence of severe hepatotoxicity, even after adjustment for TPMT genotype [62][63][64][65][66]. Furthermore, a variant in the PACSIN2 gene has been found to modulate the activity of TPMT and is also independently associated with severe gastrointestinal toxicity due to 6-MP [70].…”
Section: Gastrointestinal Toxicitymentioning
confidence: 96%
See 1 more Smart Citation
“…The ITPA variant allele (rs1127354) is associated with nonfunctionality of the enzyme and is found with an allelic frequency ranging from 5 to 19%, with the lower end of the range seen in Caucasian populations and the higher range seen in Asian populations [96]. The polymorphism is associated with higher concentrations of methylated nucleotide metabolites of 6-MP in cells, as well as higher incidence of severe hepatotoxicity, even after adjustment for TPMT genotype [62][63][64][65][66]. Furthermore, a variant in the PACSIN2 gene has been found to modulate the activity of TPMT and is also independently associated with severe gastrointestinal toxicity due to 6-MP [70].…”
Section: Gastrointestinal Toxicitymentioning
confidence: 96%
“…Polymorphisms in the ITPA, NR3C1, and PNPLA3 genes have all been implicated in severe GI toxicity with ALL treatment [31,63,95]. The ITPA enzyme is involved in 6-MP metabolism and has been implicated in its hepatotoxic effects.…”
Section: Gastrointestinal Toxicitymentioning
confidence: 99%
“…found no association with the same SNP in a smaller, retrospective study that only assessed toxicity over the first month of therapy. ATP binding cassette subfamily B member ( ABCB1 ) was studied in five studies with two demonstrating protective effects from rs4728709 and rs10244266 . Of these, Lopez‐Lopez et al.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Guitierrez-Carnino et al 24 found no association with the same SNP in a smaller, retrospective study that only assessed toxicity over the first month of therapy. ATP binding cassette subfamily B member (ABCB1) was studied in five studies 14,18,[25][26][27] with two demonstrating protective effects from rs4728709 and rs10244266. 18,25 Of these, [12][13][14] although these findings were not replicated across the cohort studies.…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Controversial results were reported in Asian populations: Kim et al [60] did not find a difference in the cumulative incidence of grade III/IV febrile neutropenia according to ITPA genotypes in Korean ALL pediatric patients whereas Malaysian patients with ITPA 94A allele seemed more prone to develop fever and liver toxicity in therapeutic protocols not individualized for TPMT [61] . An Italian pharmacogenetic multicentric study was performed on 508 pediatric ALL patients treated with the AIEOP-BFM 2000 protocol: four children were homozygous variant for rs1127354 (94 AA genotype) and had a significant 13-fold increase in the risk of developing severe (grade III-IV) neurological toxicities during the 2 months induction phase, when compared with wildtype subjects, and showed also an higher risk of developing severe gastrointestinal complications (8-fold increase in risk) [62] . However, in this study, MP were introduced only four weeks after the beginning of the treatment, thus the incidence of these adverse effects could not be uniquely ascribable to thiopurines and the contribution of other drugs, such methotrexate, could be considered.…”
Section: Itpamentioning
confidence: 99%